A suggested Model for Job description of the Agricultural Extension Workers in the Kurdistan region of Iraq - Rashid, Debar Ali; Layek, Tahir Mohamed (Sulaimani Journal for Pure and Applied Sciences, 2018)
The aim of the study was to develop a suggested model for job description of the Agricultural Extension workers in the Kurdistan region of Iraq, and identifying the current situation for job description of the Agricultural extension workers in the Kurdistan Region. Also, preparing a suggested model for job description that deal with the weaknesses and combine the new attitudes by agriculture in the Kurdistan Region of Iraq. The research populations were including the Extension Organizations which consist of (public authority for extension and agricultural research, directorates of agricultural extension in the governorates, extension centers in the Districts, Sub-districts and Villages). A convenience sample was selected for representing the managers in the extension centers were showing the (%68, 18) of (30) extension managers. Another, were selected from Agricultural Extension workers showing (%50, 20) of (120) extension workers, as well as (5) directors in the agricultural extension governorates, so the total reached (155) respondents. According to the literature and previous studies due to the subject of the research developed were two elements, eight fields and sixty eight items, formed the preliminary version of the model. The model were displayed to seventeen experts and specialists in the field of agricultural extension, management and psychological sciences, to judge the validity and importance of what came in the table of characteristics, according to the elements, fields and items selected earlier, experts can judge how much the table is appropriate and valid. The following statistical techniques were used in data analysis: replicates, percentages, means, range, weighted arithmetic mean, correction factor, chi square test, percentile weight, Alpha-Chronbach Coefficient method and t-test. The research results reached that; unclear of the agricultural extension work in the workers, because lack of duties in the job description for workers in the governorates of the Kurdistan. The research reached to a conclusion that; all those contained in this study were in agreement with the (79) items of suggested model, distributed over (8) fields and (2) elements (qualifications, tasks). The recommendations were applied of the suggested model in the current situation of the work of agricultural extension in the Kurdistan Region with providing all the requirements to make it a successfully.
Keywords: Job description